Risk management and communication in informal dairy sector in Côte d’Ivoire: Options for sustainable livelihoods - Traoré, S.; Gboko, T.; Sanhoua, A.; Kirioua, J.; Dao, D.; Jans, C.; Hattendorf, J.; Meile, L.; Lacroix, C.; Bonfoh, Bassirou (Centre Suisse de Recherches Scientifiques, 2015)
Intervention in food and nutrition was the best investment for our collective future in terms of managing co-morbidity in population. This investment should combine agricultural system with health and education. Fermented dairy products (FDP) played an important role for prolonged shelf life, microbial safety and nutrition. FDP was proved to be contaminated in Kenya, Somalia, Mali and Côte d'Ivoire by foodborne pathogens including Staphylococcus aureus and Escherichia coli. Recently, it was showed that FDP was predominated by a novel Streptococcus infantarius subsp. infantarius (Sii) variant. Sii-produced bacteriocin and fermentation activity could contribute to the suppression of pathogens and possibly mitigate socioeconomic and health risks. However, Sii as member of Streptococcus bovis group was associated with human and animal infections. Therefore, a potential application of Sii as adapted African starter culture for enhanced food safety required a thorough safety assessment. In order to improve hygiene and quality as well as to increase production for school canteens, urban consumption and sustainable livelihoods, a cross-sectional study was conducted in Korhogo (Côte d’Ivoire) from May to August 2014. The objective was to assess local technologies and the dairy value chain in relation to Sii prevalence, followed by a participatory stakeholder workshop to validate findings and derive adapted interventions. The study showed that the dairy value chain contributed to livelihoods and household income. About 90% of milk produced (range: 12-44 liters/collector) were sold via collectors, generating 6-20 Euros per day shared among herder, collector and vendor. The remaining 10% were consumed within the household. However, dairy production was low and scattered due to informal practices resulting in poor quality product. Basic hygiene such as cleaning, washing, disinfecting was lacking. Milk quality depreciated with the local practices, access to clean water and energy. Future interventions identified by stakeholders comprised (i) awareness on local dairy hygiene and nutritional value for the population especially school children, (ii) stakeholders organization around cooperative to develop sustainable dairy model (public dairy with private management); (iii) promote healthy milk products for school canteen programme in Korhogo through adapted local dairy technology.